Redox chemistry of uranium in reducing, dilute to concentrated NaCl solutions. (November 2018) - Çevirim-Papaioannou, Neşe; Yalçıntaş, Ezgi; Gaona, Xavier; Dardenne, Kathy; Altmaier, Marcus; Geckeis, Horst
Abstract: The redox behaviour of uranium was investigated in 0.1 and 5.0 M NaCl solutions at 2 ≤ pHm ≤ 14.5 (pHm = –log [H + ]) in the presence of different reducing chemical systems (Sn(II), Na2 S2 O4, Sn(II) + TiO2, Sn(II) + Fe(0), Sn(II) + Fe3 O4 ). All experiments were performed under Ar atmosphere at T = (22 ± 2) °C. Uranium was added to independent batch samples as U(VI) (with [U]0 = 3.0⋅10 −5 or 4.2⋅10 −4 M), and the evolution of uranium concentration monitored for t ≤ 635 days. After attaining equilibrium conditions, [U] was found in all cases clearly below the solubility of U(VI) solid phases (UO3 ⋅2H2 O(cr) or Na2 U2 O7 ⋅H2 O(cr)) and in good agreement with the solubility of tetravalent UO2 (am, hyd) as calculated with available thermodynamic data. This observation is in line with (pe + pHm ) measurements, which in all cases fell in the stability field of U(IV). Solvent extraction and XANES confirmed also that uranium is predominantly found as U(IV) in the aqueous and solid phases investigated. No evidence on the formation of anionic hydrolysis species of U(IV) was obtained up to pHm = 14.5. Based on our long-term redox study, we conclude that previous investigations reporting the formation of U(OH)5 – and U(OH)6 2− are possibly flawed by insufficient equilibration time, which prevented the complete reduction of U(VI) to U(IV). Our results further confirm that experimental pHm and E h values measured in buffered systems can be considered as reliable parameters to predict the redox behaviour of U in dilute to concentrated NaCl systems. Highlights: Complete reduction of U(VI) observed in reducing systems with 2 ≤ pHm ≤ 14.5. Final uranium concentration in excellent agreement with solubility of UO2 (am, hyd). Predominance of U(IV) confirmed also by XANES and solvent extraction. Reduction kinetics strongly affected by pe, pH, [U(VI)]0, [reductant] and [Na]. Formation of U(IV) anionic hydrolysis species excluded for systems with pHm ≤ 14.5.